Measuring The Benefits of Euro Area Membership - Chankov, Georgi (Research Papers, 2023)
Membership in the euro area should bring advantages to member states. These can only be proven in a comparison between countries on both sides of the “currency border”. The Netherlands, Sweden, Belgium, Denmark and Finland are selected as highly developed welfare states with similar social and economic characteristics. The combination of sociological and economic indicators should overcome the limitations of the technocratic approach. Data from the selected broad set of socio-economic indicators over a sufficiently long period of time, including a period of crisis and recovery, provides a good enough empirical basis for analysis. Tracking these indicators over the period from 2000 to 2021 does nothing to prove the advantages of euro area membership.